2006
DOI: 10.1039/b611741b
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heme proteins using atomistic simulations

Abstract: Heme proteins are found in all living organisms, and perform a wide variety of tasks ranging from electron transport, to the oxidation of organic compounds, to the sensing and transport of small molecules. In this work we review the application of classical and quantum-mechanical atomistic simulation tools to the investigation of several relevant issues in heme proteins chemistry: (i) conformational analysis, ligand migration, and solvation effects studied using classical molecular dynamics simulations; (ii) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 205 publications
1
83
0
Order By: Relevance
“…However, attempts to predict the ground state multiplicity of these systems soon made apparent that an accurate description of the spin state might require more sophisticated techniques [47]. This fact can be tracked down to the fact that it has been systematically observed that Hartree-Fock favors high-spin electronic configurations while DFT exhibits a preference for low-spin states [48,49]. These well known DFT flaws, however, are not expected to affect the comparative analysis performed in this work between different P 460 model systems.…”
Section: Methodsmentioning
confidence: 97%
“…However, attempts to predict the ground state multiplicity of these systems soon made apparent that an accurate description of the spin state might require more sophisticated techniques [47]. This fact can be tracked down to the fact that it has been systematically observed that Hartree-Fock favors high-spin electronic configurations while DFT exhibits a preference for low-spin states [48,49]. These well known DFT flaws, however, are not expected to affect the comparative analysis performed in this work between different P 460 model systems.…”
Section: Methodsmentioning
confidence: 97%
“…All MD simulations were performed using the AMBER package [25], with the ff99 force field implementation. The heme parameters were taken from previous work [26].…”
Section: Set Up Of the Systemmentioning
confidence: 99%
“…Depending on subtle modifications on the porphyrin environment generated by the protein backbone, the same heme prosthetic group, mostly heme b, may have a different biochemical behavior [7]. The effect of the protein environment can be classified into four main groups: (1) distal amino acid coordination to the metal center, (2) induction of geometric distortions by steric/electrostatic effects, (3) interaction of amino acids with ligands and (4) electronic effect of proximal amino acids on the porphyrin macrocycle [8,9]. The first and second effects are relevant when considering isolated metalloporphyrins as catalysts; the third and fourth effects have been mimicked in many examples in the model porphyrin literature by intramolecular interactions in tailored synthetic porphyrins and by electron withdrawing or donating substituents, respectively [10].…”
Section: Introductionmentioning
confidence: 99%